Новые подходы преподавания в обучении учащихся, через внедрение в практику работы школы подхода lesson study - Апрелова, О. А. (My University, 2016)
The possibility of use in the practice of teachers of a new approach to learning Lesson Study, conducted in the framework of the professional community, allows you to see the difference between what, in the opinion of teachers, should take place during children's education, and what is happening in reality. Implement approach Lesson Study as part of the professional community of teachers, which is a priority goal of helping students in education and vocational training team members.
Keywords: A new approach; the study of the lesson; Lesson Study; assistance in learning and teaching